Identificación de parásitos mediante exámenes coproparasitarios en Canis lupus familiaris, durante la campaña de salud preventiva del programa de tenencia responsable de mascotas de la UDLA, en el sector Puengasí - Ramos Checa, Nicole Sthefania (2020)
Currently internal parasites in dogs represent a zoonosis problem for pet owners, therefore the justification of this study is based on improving the health conditions of the dogs with adequate deworming processes, the main objective of this study is the identification of parasites by means of co-parasite examinations in Canis lupus familiaris, during the preventive health campaign of the responsible pet ownership program of the University of the Americas, specifically in the Quito canton in the Puengasí parish. The study has an experimental approach of longitudinal cut, so within its methodology clinical records of each dog were collected, faecal samples were taken to identify the species and parasite load through stool tests, and then administer dewormers according to the parasitic agent present, this was carried out in two groups of dogs from two neighborhoods in the same sector, the results correlated the demographic characteristics of the dogs with the presence of parasitic agents (Entamoeba spp., Ancylostoma spp., Toxocara canis), who noted that the presence of these was greater in the population of female, juvenile and mixed breed dogs. The sample included a total of 103 dogs, among them 61 dogs from the Barrio la Lorena and 42 dogs from the Balcón del Valle neighborhood. For the statistical analysis, we worked with the variables of sex, age, phenotype and parasite species, in relation to the neighborhood to which each dog belonged; and with the Chi-square test it was possible to identify whether or not there is a dependency between the studied variables, allowing to analyze if there is a direct relationship between them. In the discussion, the high influence of the environment on the presence of parasites was analyzed in relation to the results obtained. In conclusion, the importance of the identification of parasitic agents prior to deworming processes could be pointed out, the parasites identified in all the dogs were: Entamoeba spp., Ancylostoma spp., Toxocara canis, which are zoonotic and can be transmitted to humans causing damage to your health.